2009
DOI: 10.4314/eajph.v6i1.45735
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age At Birth And Under-5 Mortality In Nigeria

Abstract: Objective: The paper examined the impact of maternal age at birth on under-5 death in Nigeria. Method: Secondary data were generated from the 2003 Nigeria Demographic and Health Surveys in examining the relationship between maternal age at birth and under-5 mortality risk. Relationships between variables were tested through bivariate and logistic analyses. Results: Out of 7620 sampled women for the study, almost 60% were less than 30 years old, the median age was 26 years-a youthful population. Analyses of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…We found that majority of the parents/caregivers have poor knowledge (41%), attitude (55%) and practice (40%). The same studies were conducted in India 15 and Nigeria 16 and found nearly same results. This may be as a result of poor awareness program at community level or rural areas and about 92% suggested for awareness campaign among parents/caregivers as well as community level to improve ROP KAP.…”
Section: Discussionsupporting
confidence: 66%
“…We found that majority of the parents/caregivers have poor knowledge (41%), attitude (55%) and practice (40%). The same studies were conducted in India 15 and Nigeria 16 and found nearly same results. This may be as a result of poor awareness program at community level or rural areas and about 92% suggested for awareness campaign among parents/caregivers as well as community level to improve ROP KAP.…”
Section: Discussionsupporting
confidence: 66%
“…None also volunteered a family history of psychiatric illness. This is not the usual finding in the literature [ 5 , 14 , 16 , 20 , 23 ] where the risk of postpartum psychosis has been shown to be increased in families with a history of bipolar disorder. However, a lot of stigmas are attached to psychiatric illnesses in Africa as a whole; thus most people will not willingly volunteer such information.…”
Section: Discussionmentioning
confidence: 55%
“…This finding differs from that of a study in Sweden which found that older maternal age was associated with increased risk of first hospital admission from postpartum psychosis among first-time mothers [ 15 ]. This difference may be because the average age at first birth in Nigeria is less than 19 years [ 16 ] and primiparity is reported as a risk factor for postpartum psychosis [ 1 , 5 , 6 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to investigate and understand the risk factors for infant and child mortality abound with factors such as maternal age at the birth of the child [ 5 , 6 ], maternal education [ 1 ], parity [ 7 , 8 ], family size [ 9 ], birth interval [ 9 , 10 ], access to health care [ 11 ], and factors surrounding the prenatal and postnatal periods being implicated to varying degrees. Though these risk factors have been implicated in various studies, it is worth noting that their distribution in time, place, and person varies from locality to locality.…”
Section: Introductionmentioning
confidence: 99%